STRATEGI PENGEMBANGAN TEMPAT PELELANGAN IKAN (TPI) DOBO DI KABUPATEN KEPULAUAN ARU - Abrahamsz, James; Lainata, Monalisa C; Tetelepta, Johannes M S; Pattikawa, Jesaja A; Tuapetel, Friesland (TRITON: Jurnal Manajemen Sumberdaya Perairan, 2024)
The Dobo Fish Auction Place in Aru Islands Regency, is the center of fishermen's activities with good opportunities and prospects if properly utilized, it will make a great contribution to the welfare of fishermen and to the Regional Government. In its implementation, the role of institutions is very important in the management of TPI Dobo. The purpose of this study is to analyze the institutional management of TPI Dobo, as well as provide recommendations for management direction in managing TPI Dobo in Aru Islands Regency so that it is sustainable. This research was carried out from January to May 2024 at TPI Dobo, Aru Islands Regency. The data in this study was collected by observation, interview, and documentation methods. The analysis method used is qualitative descriptive using the management function theory. The results of the analysis on the indicators of planning, organizing, implementation and supervision are not optimal yet, and there are 3 strategies out of 8 strategies that are prioritized as management directions of the Fish Auction Place in Dobo, Aru Islands Regency. ABSTRAK Tempat Pelelangan Ikan (TPI) Dobo di Kabupaten Kepulauan Aru, merupakan sentral kegiatan nelayan dengan peluang dan prospek yang baik. Apabila dimanfaatkan dengan semestinya maka TPI ini akan memberikan kontribusi yang besar bagi kesejahteraan nelayan maupun kepada Pemerintah Daerah Kabupaten Kepulauan Aru. Dalam pelaksanaannya, peran kelembagaan sangat penting dalam pengelolaan TPI Dobo. Tujuan penelitian ini adalah untuk menganalisis manajemen kelembagaan TPI Dobo, serta memberikan rekomendasi arahan pengelolaan dalam mengelola TPI Dobo di Kabupaten Kepulauan Aru agar berkelanjutan. Penelitian ini dilaksanakan pada Januari-Mei 2024 di TPI Dobo, Kabupaten Kepulauan Aru. Data pada penelitian ini dikumpulkan dengan metode observasi, wawancara dan dokumentasi. Metode analisis yang digunakan adalah deskriptif kualitatif menggunakan teori fungsi manajemen. Hasil analisa pada indikator perencanaan, pengorganisasian, pelaksanaan dan pengawasan tergolong belum optimal, serta terdapat 3 strategi dari 8 strategi yang merupakan prioritas sebagai arahan pengelolaan TPI Dobo, Kabupaten Kepulauan Aru. Kata Kunci: TPI, kelembagaan, pengelolaan, Dobo, Kepulauan Aru